Pre-operative prediction of cholesteatomas from radiology: retrospective cohort study of 106 cases. Issue 6 (7th June 2019) - Selwyn, D; Howard, J; Cuddihy, P
Abstract: Objective: Pre-operative imaging is often used to predict the extent of a cholesteatoma and anatomical variation to plan for surgery. This study aimed to measure the predictive accuracy of computed tomography findings. Methods: A retrospective cohort study was conducted of all patients in a district general hospital undergoing mastoid surgery within a consecutive 12-month period, in whom computed tomography had been performed prior to operative intervention. The study measured the key findings of pre-operative computed tomography imaging and compared them to the intra-operative findings. Results: A total of 106 patients were included. The sensitivity and specificity for predicting cholesteatoma were 79 per cent and 81 per cent respectively. The positive predictive value was 90 per cent and the negative predictive value was 65 per cent. In predicting complications of cholesteatomas, the sensitivity was 70 per cent, whereas the specificity was 91 per cent. The positive predictive value was 88 per cent and the negative predictive value was 76 per cent. Conclusion: Pre-operative computed tomography conducted prior to mastoid surgery has high positive predictive values for both predicting cholesteatomas and complications (90 per cent and 88 per cent respectively).